Vitamin D status contributes to the antimicrobial activity of macrophages against Mycobacterium leprae. - Elliot W Kim; Rosane M B Teles; Salem Haile; Philip T Liu; Robert L Modlin (Public Library of Science (PLoS), 2018)
BACKGROUND:The immune system depends on effector pathways to eliminate invading pathogens from the host in vivo. Macrophages (MΦ) of the innate immune system are armed with vitamin D-dependent antimicrobial responses to kill intracellular microbes. However, how the physiological levels of vitamin D during MΦ differentiation affect phenotype and function is unknown. METHODOLOGY/PRINCIPAL:The human innate immune system consists of divergent MΦ subsets that serve distinct functions in vivo. Both IL-15 and IL-10 induce MΦ differentiation, but IL-15 induces primary human monocytes to differentiate into antimicrobial MΦ (IL-15 MΦ) that robustly express the vitamin D pathway. However, how vitamin D status alters IL-15 MΦ phenotype and function is unknown. In this study, we found that adding 25-hydroxyvitamin D3 (25D3) during the IL-15 induced differentiation of monocytes into MΦ increased the expression of the antimicrobial peptide cathelicidin, including both CAMP mRNA and the encoded protein cathelicidin in a dose-dependent manner. The presence of physiological levels of 25D during differentiation of IL-15 MΦ led to a significant vitamin D-dependent antimicrobial response against intracellular Mycobacterium leprae but did not change the phenotype or phagocytic function of these MΦ. These data suggest that activation of the vitamin D pathway during IL-15 MΦ differentiation augments the antimicrobial response against M. leprae infection. CONCLUSIONS/SIGNIFICANCE:Our data demonstrates that the presence of vitamin D during MΦ differentiation bestows the capacity to mount an antimicrobial response against M. leprae.